Euro Area Policies. (IMF Staff Country Reports; Country Report ;, 2003)
The continuing weakness of activity in the euro area reflects an amalgam of cyclical and long-term forces that are likely to shape the outlook and to challenge policies. Financial conditions in the area have improved along with those in global markets, though financial fragilities may be impairing the transmission to firms. The aging of the population could entail significant declines in potential output growth and lower expected lifetime income resources. Forward-looking policies are needed to improve the quality and ensure long-term sustainability.